Russian Federation : Selected Issues. (IMF Staff Country Reports; Country Report, 2006)
Russia's large oil and gas reserves play a key role in its economic development. As with many other large oil exporters, Russia's energy wealth is also posing numerous challenges to macroeconomic management. Although fiscal policy has saved a large part of the oil windfall in the Oil Stabilization Fund (OSF), this has not been guided by a consistent long-term framework. The framework is illustrated with numerical simulations of different fiscal spending rules that are consistent with sustainable paths of consumption out of oil and gas wealth over time.